Clinical impact of the sequentially‐checked drain removal criteria on postoperative outcomes after pancreatectomy: a retrospective study. (23rd July 2019) - Kosaka, Hisashi; Satoi, Sohei; Yamamoto, Tomohisa; Hirooka, Satoshi; Yamaki, So; Kotsuka, Masaya; Sakaguchi, Tatsuma; Inoue, Kentaro; Matsui, Yoichi; Sekimoto, Mitsugu
Abstract: Background: Strict criteria for impeccably safe drain management following pancreatectomy have not yet been developed. We evaluated the utility of the sequentially‐checked drain removal criteria by comparison with conventional criteria. Methods: Postoperative outcomes of 801 patients who underwent pancreatectomy, including 395 patients for whom drain fluid amylase (DFA) < 375U/l on postoperative day (POD) 3 (control group), were used and 406 patients for whom the sequentially‐checked criteria of DFA <5, 000 U/l on POD 1 and DFA <3, 000 U/l on POD 3 (sequentially‐checked group) were used and were retrospectively evaluated. Results: DFA on POD 3 and fistula risk score did not differ between groups. Significantly more patients in the sequentially‐checked group met the criteria (control, 63.8% vs. sequentially‐checked, 76.1%, P  <   0.001). The incidences of clinically relevant postoperative pancreatic fistula (CR‐POPF) (17.0% vs. 11.1%), intra‐abdominal abscess (21.0% vs. 9.1%) were significantly lower in the sequentially‐checked group (all P  <   0.05). Multivariate analysis revealed that use of the sequentially‐checked criteria was significantly associated with CR‐POPF (odds ratio 0.601, 95% confidence interval [CI] 0.389–0.929; P  =   0.022). C‐reactive protein <15 mg/dl at POD 3 was identified as an independent predictive factor for false positive CR‐POPF results in the sequentially‐checked group (odds ratio 0.872, 95% CI 0.811–0.939; P  <   0.001); thus, this criterion was added to create the new triple‐checked criteria. Conclusions: The sequentially‐checked criteria can provide safe drain management and improve postoperative outcomes. Abstract : Highlight Kosaka and colleagues set out to evaluate the utility of the sequentially‐checked drain removal criteria following pancreatectomy by comparison with conventional criteria. The sequentially‐checked criteria significantly decreased the incidence of clinically relevant postoperative pancreatic fistula, intra‐abdominal abscess, and percutaneous abscess drainage, suggesting they may contribute to safer postoperative management after pancreatectomy.